Penggunaan Metode Demonstrasi dalam Peningkatan Hasil Belajar Siswa pada Standar Kompetensi Menggunakan Hasil Pengukuran (MHP) Kelas XII TEI Semester Ganjil di SMKN 4 Kota Serang Tahun Pelajaran 2021/2022 - Netriwita, (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2022)
This study aims to describe the process and outcomes of learning through the use of the Demonstration method. The research method employed was Action Research, which consisted of four stages: planning, action, observation, and reflection. The study was conducted in two cycles and the participants were 31 twelfth grade students (26 boys and 5 girls) from a Vocational Education School (SMK). Data was collected through observation notes and analyzed using both qualitative and quantitative methods. The results indicate an increase in learning outcomes after the implementation of the demonstration method. Daily test assessments revealed a 67.90% learning outcome in cycle one and 78.50% in cycle two, resulting in a 10.6% increase between the two cycles. Furthermore, student participation during the learning process also increased, with a percentage of 26.09%. These findings suggest that the demonstration method is effective in improving student learning outcomes and increasing student engagement.